2019
DOI: 10.1016/j.afos.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy in actual clinical practice of once-weekly subcutaneous teriparatide for osteoporosis patients with a high fracture risk

Abstract: Objectives To reassess the safety and efficacy of once-weekly teriparatide 56.5 μg in osteoporosis patients with a high fracture risk. Methods This postmarketing observational study was conducted at 72 weeks according to the package insert. Of the 3573 Japanese osteoporosis patients in the safety analysis set, 91.80% were women, the mean age was 78.1 years, and 69.89% had a history of prevalent fragility fractures, indicating that a high proportion of patients at high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
(16 reference statements)
1
5
1
Order By: Relevance
“…Data shown in the paper reported by Omura [1] and that by Ifuku et al. [2] might be in line with those in the phase 2 clinical trial [3], although data of bone metabolic markers before 24 weeks of the treatment were not available in either report.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…Data shown in the paper reported by Omura [1] and that by Ifuku et al. [2] might be in line with those in the phase 2 clinical trial [3], although data of bone metabolic markers before 24 weeks of the treatment were not available in either report.…”
supporting
confidence: 58%
“…At this moment, once-weekly teriparatide is available in Japan and South Korea. Two independent papers focusing on once-weekly teriparatide in daily clinical practice are published in this issue of Osteoporosis and Sarcopenia [1,2]. Both of them have demonstrated that bone resorption markers did not increase with once-weekly teriparatide injections [1,2].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The once-weekly regimen was developed with less stimulation of bone resorption, compared to the effect of the once-daily regimen that leads to marked increases in the markers of both bone formation and resorption [21][22][23][24] . Patients receiving the once-weekly regimen must either be outpatients or inpatients, while the once-daily regimen can be self-administered by the patient as a home recuperation treatment 25,26 . Therefore, the twice-weekly regimen with a selfinjection device that was recently approved in Japan is expected to reduce the burden on patients from both hospital visits and frequent self-injection 22 .…”
Section: Introductionmentioning
confidence: 99%